Bandwagon effects in high-technology industries - Rohlfs, Jeffrey H. (MIT Press, 2001)
Economists use the term "bandwagon effect" to describe the benefit a consumer enjoys as a result of others' using the same product or service. The history of videocassettes offers a striking example of the power of bandwagon effects. Originally there were two technical standards for videocassettes in the United States: Beta and VHS. Beta was widely regarded to have better picture quality, but VHS could record longer television programs. Eventually the selection of Beta cassettes shrank to zero, leaving consumers no choice but to get on the VHS bandwagon. The most successful bandwagon, apart from telephone service, is the Internet. In this book, Jeffrey Rohlfs shows how the dynamics of bandwagons differ from those of conventional products and services. They are difficult to get started and often fail before getting under way. A classic example of a marketing failure is the Picturephone, introduced by the Bell System in the early 1970s. Rohlfs describes the fierce battles waged by competitors when new services are introduced, as well as cases of early agreement on a single technical standard, as with CDs and CD players. He also discusses the debate among economists and policy analysts over the advantages and disadvantages of having governments set technical standards. The case studies include fax machines, telephones, CD players, VCRs, personal computers, television, and the Internet.